Analisis Kualitas Bioetanol Dari Kulit Pisang - G M Saragih; Hadrah Hadrah; Dilla Tri Maharani (Jurnal Daur Lingkungan, 2021)
Indonesia is ranked sixth in banana production with total production in 2015 of 7.299.275. the more people who like bananas, the higher the volume of banana peel waste produced. Banana peels are usually thrown away immediately and can contaminate the soil surface because banana peels contain acid so that it can have an impact on evironmental problems. The starch content of banan peels has the potential to be used as a raw material for bioethanol production with the help of the fermentation process. Therefore this research aims to determine the quality of bioethanol which is produced from several types of banana peels. The types of banana peels used are Ambon banana peel, Barangan banana peel and horn banana peel. The method used to manufacture bioethanol form the types of banana peel of ambon, barangan and horn is fermentation using yeast tape or saccharomyses cereviciae. The variables observed in this study were the variety of banana peel types, fermentation time for 6 days and 10 days, and the use of yeast as much as 5 grams. The fermentation results in the form of bioethanol were analyzed using gas chromatography, the best results from this study were obtained on the type of banana peel of Ambon for 10 days, that is 4.451% bioethanol.